2020
DOI: 10.15420/ecr.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Maternal Adverse Outcomes in Pregnant Women with Cardiac Disease in Low-resource Settings

Abstract: Background: Cardiac disease is an important life-threatening complication during pregnancy. It is frequently seen in pregnant women living in resource-limited areas and often results in premature death. Aim: The aim of this hospital-based longitudinal study was to identify factors related to adverse maternal and neonatal outcomes in pregnant women with cardiac disease in low-resource settings. Methods: The study enrolled 91 pregnant women with congenital or acquired cardiac disease over a period of 2 years in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The rate of pulmonary edema in our study was 13.7% which was similar to that of P. A. Poli et al [33] (16.7%) and J. Relmasira et al [34] (11.1%). However, significantly higher rates of pulmonary edema were reported by Silverside et al [36] (31.25%) and Desia et al [37] (35%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The rate of pulmonary edema in our study was 13.7% which was similar to that of P. A. Poli et al [33] (16.7%) and J. Relmasira et al [34] (11.1%). However, significantly higher rates of pulmonary edema were reported by Silverside et al [36] (31.25%) and Desia et al [37] (35%).…”
Section: Discussionsupporting
confidence: 90%
“…On the Other hand, Samii et al [32] found that the NYHA class changed during pregnancy in 26.3% of patients, mostly in the third trimester. ICU admission was 23.5% in the present study compared with 6.3% in Pilo et al's study [33] , which can be related to the proportion of patients with severe MS. In our study, pulmonary hypertension was seen in 9.8% of pregnant women with MS, which was similar to that of J. Relmasira et al [34] (8.3%) and Pilo et al [25] (10.5%).…”
Section: Discussioncontrasting
confidence: 60%
“…in this setting, 80% delivered vaginally, 18.5% had undergone C-section and 4.6% underwent termination of pregnancy for miscarriage. 5 In our study, from 12 cases one was diagnosed during intra-partum, one was diagnosed in post-partum period while rest of the cases were identified in ante-natal period.…”
Section: Discussionmentioning
confidence: 56%
“…7,12,15 A study published in European Cardiology Review (ECR) by Poli et al reported maternal death to be slightly higher at 12%. 16 Causes of death were acute pulmonary edema and congestive cardiac failure. In maternal mortality, highest incidence of death was in patients of dilated and peripartum cardiomyopathies.…”
Section: Discussionmentioning
confidence: 99%